Factors Affecting Child Immunization In Indonesia Based On Indonesia Demographic Health Survey (IDHS) 2012 - Furqon, Ufi Alaia; Estudillo, Jonna P (Prodi Magister Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat Undip, 2018)
Immunization programs have contributed to prevent the spread of infectious diseases and mortality among children. Although Indonesia has experienced remarkable progress in reducing child mortality, universal immunization coverage has not been achieved. This paper aims to identify important factors affecting the incidence of child immunization in Indonesia using the Indonesia Demographic and Health Survey (IDHS) of 2012. By probit regression, I estimated the child immunization acceptance and analyzed the impact of location of households at the provincial level which divide the location of respondents both inside and outside of Java. I found that mother’s level of education, household assets, and urbanity are important factors affecting the uptake of vaccinations. In addition, significant regional differences in vaccination incidence indicated that local resources serve as bottlenecks in vaccination. By encouraging government policies that improve women’s schooling, household assets, and regional support for health, vaccination coverage could increase and even become universal.